EVALUASI IMPLEMENTASI KEBIJAKAN STANDAR SARANA DAN PRASARANA LABORATORIUM FISIKA SMA NEGERI 2 KOTA TANGERANG SELATAN - Waramatias Waramatias (Jurnal Manajemen Pendidikan, 2016)
The objective of this research was to evaluate (1) compliance of physics laboratory building requirement and conditions with standard and (2) fulfillment of physics laboratory furniture and practicum equipments at Public Secondary School No. 2 Kota Tangerang Selatan. The method used in the research was qualitative descriptive method with Provus’s discrepancy evaluation model (DEM). The data were collected through observation, interview, and document study. Data analysis and interpretation show that the laboratory building (1) did not have a full accordance with safety, healthy, comfort, access easiness, and size and room adequacy tandards in input, process, and output components, and (2) did not fully fulfill types and quantity of furniture, materials and basic measurement tools, practicum kits, educational media, and other equipments in input, process, and output components. The findings lead to recommendation that SMAN 2 Kota Tangerang Selatan should equip its physics laboratory building to meet requirements and conditions in effect and should fulfill its physics laboratory furniture and practicum equipment set in the standard.